Assessing psychomotor abilities in handcyclists using computerized tests: an initial study - Pasko, W.; Dydek, J.; Zielinski, J.; Hulewicz, T.; Sliz, M.; Dziadek, B.; Przednowek, K. (Proceedings of the 10th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2022)
Psychomotor abilities play an important role in any sport, they affect the speed of decisions made in a given situation, and thus can have a direct impact on the final outcome of sports competition. The study included ten disabled handcyclists who represented Poland internationally in the H2, H3, H4 and H5 categories. The control group consisted of non-disabled 5th year physical education students at the University of Rzeszow. The research methods were psychomotor tests using computer techniques in the Test2Drive system. For the evaluation, the tests performed were: simple reaction time (SIRT), complex reaction time (CHORT), hand-eye coordination (HECOR) and spatial orientation (SPANT). Reaction time (RT), motor time (MT) and correct responses (c.r.) were analyzed. The group of disabled cyclists is characterized by better motor time in each test while no statistical significance was shown. A better reaction time in each psychomotor test was achieved by the control group and the diffe rences are statistically significant. Better motor time may suggest that cycling training has a positive effect on psychomotor abilities.